Sex of the calf according to the ovary of ovulation in llamas (Lama glama) of the Argentinean Puna - Abalos, Marcos C. (2023)
The aim of this work was to determine the sex ratio of the offspring born from ovulations of the left or right ovaries in naturally mated llamas. Females (n=188) with the presence of an ovarian follicle ≥7 mm received controlled natural mating (Day 0). Ovulation was confirmed on day 2 by the disappearance of the ovarian follicle (n=146). Then, 104 (71.2%) females diagnosed pregnant by ultrasonography were obtained 40-45 days after mating. The mating and calving date, sex and body weight of the calf at birth were recorded in 92 individuals. The overall sex ratio of the offspring and the sex ratio of the offspring from each ovary were compared using the Chi-square goodness-of-fit test, with the expected ratio being 1:1. Ovulations from both ovaries produced a similar (p=0.14) proportion of calves born and the male: female ratio was similar. However, more male offspring originated from the left ovary than from the right (65.2 vs. 34.8%, respectively; p=0.04), although the percentages of males born originated from ovulations from the left ovary (30/53=56.6%; p=0.33) and right ovary (16/39=41.0%; p=0.26) were not different from the expected ratio (1:1). The length of gestation and live weight at birth were statistically similar between sexes.